Responding to COVID-19 Pandemic: Applying the Dynamic Capability Framework in University Libraries - Owusu-Ansah, S.; Walt, T. van der (University of Ghana, 2021)
To continue to remain the backbone in research-intensive universities and centre for educational excellence, academic libraries must have the capacity to renew library competences to respond rapidly and promptly towards the new global health crisis, and effectively adapt, integrate, and reconfigure the internal and external organizational repertoire to match the needs of users. During COVID-19 pandemic, academic libraries need to be innovative and operate more virtual than traditional. The dynamic capability framework assists library managers and policymakers in recognizing aspects of enhancement capacity that require improvement. In conclusion, the dynamic capability framework is an optimal decision-making alternative for library management and academic libraries in the context of isolation, quarantine, and physical distance during the COVID-19 era.
Book Chapter
Keywords: Information and Communication Technology; Re-Positioning; Academic Libraries; Digital Age; Realignment; Strategic Re-Positioning; Digital Library Services